Hvordan skildres generisitet i norsk faglitteratur? - Kurek, Anna (Folia Scandinavica Posnaniensia, 2017)
This paper aims to examine how genericity is described in the Norwegian specialised literature concerning Norwegian Bokmål. Genericity is a grammatical (and to some extent semantic) phenomenon that can be expressed in different ways. In Germanic languages, including Norwegian, genericity is expressed by the use of both definite and indefinite articles, as well as bare nouns. In Norwegian, all five noun forms (namely bare noun, indefinite and definite singular forms and indefinite and definite plural forms) can be used to express a generic reference. The choice of a given noun form depends mainly on the context and the verb phrase used in a sentence. The examined materials discuss the phenomenon in a rather cursory way. Examples presented in the analysed books are mainly artificial and/or translated from the world literature on the subject. Such approach to the problem shows the lack of corpus-based research on genericity in Norwegian, which can be an interesting area to work on.